Analysis and design of a student information system case study : Hasanuddin University, Indonesia - Suarga; Radok, Rainer; Vilas Wuwongse; Weber, Karl E.; Hasanudding University - ADB Loan (Bangkok : Asian Institute of Technology, 1983)
This study develops a computer-based, online, interactive information system, geared to satisfy student information requirements of an academic institution, in particular of Hasanuddin University in Indonesia. The system comprises five subsystems, twenty eight linked data files, twenty one input forms relating to students, teachers, courses, alumni and curricula. Thirty seven reports are generated and distributed to the academic community to improve its operations, planning, control and decision making. More than sixty programs are required to meet these requirements.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1983
Keywords: Information storage and retrieval systems -- Education